Citotoxicidade e ação anti-inflamatória in vitro do extrato hidroalcoólico de Libidibia ferrea e do ácido gálico - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Popularly known as '' jucá '' or '' pau-ferro '', a Libidibia ferrea L. is a plant species widely used in traditional medicine for the treatment of various diseases, therefore, demonstrating several therapeutic properties such as antimicrobial, antioxidant activity and anti-inflammatory. Phytochemical studies highlight the presence of one of the possible responses for some of these biological activities, the gallic acid, polyphenol found in several plants, which is used as one of the main markers for control studies of Libidibia ferrea L. objective to evaluate in vitro the cytotoxicity and anti-inflammatory activity of a 7.5% (w / v) extract of Libidibia ferrea L. on RAW 264.7 macrophages and human peripheral blood monocytes. The evaluation was carried out through the MTT colorimetric assay (3- [4,5-dimethylthiazolyl-2] -2,5-diphenyltetrazolium bromide) and indirect quantification of nitric oxide (NO) by the Griess method. The culture of RAW 264.7 macrophages and the primary cells of human peripheral blood monocytes were handled in culture media, which were subsequently challenged with Escherichia coli LPS (Lipopolysaccharide), and treated with the hydroalcoholic extract of Libidibia ferrea L. and gallic acid for 24h. The assays were first performed on RAW 264.7 macrophages, to obtain the minimum and non-cytotoxic practices possible to inhibit NO production. They were divided into six groups: extract of Libidibia ferrea L. should from 1.56 μg / mL to 100 μg / mL, gallic acid 3.125 μM to 100 μM, positive control (LPS), negative control (culture medium), and the standard drug (20 µg / mL dexamethasone). Once the minimal non-cytotoxic and inhibitory options were obtained in the macrophages, the same assays were performed in human peripheral blood monocytes with the same six groups, but with L.ferrea extract in the 50 and 100 μg / mL procedures, and the 6.25 μM gallic acid. An analysis of variance of the data was performed using the ANOVA tests, followed by the Tukey and Dunnett test, with a statistically significant difference when p˂0.05. In macrophages, the tested concentrations of 1.56 μg / mL to 100 μg / mL of L.ferrea extract, none compromised cell viability, whereas in the tested concentrations of gallic acid from 3.25 μM to 100 μM, only concentrations of 3.125 μM and 6.25 μM kept the cells viable. In the quantification of NO, the extract of L.ferrea at 50 and 100 μg / mL and the gallic acid at 6.25 μM, obtained the most satisfactory results in the inhibition of NO production, considering minimum non-cytotoxic and anti-inflammatory concentrations . In the monocytes of primary culture, the results obtained in the macrophages RAW 264.7 were maintained, highlighting these samples on an anti-inflammatory potential. It can be concluded that the extract of Libidibia ferrea L. and gallic acid presented non-cytotoxic concentrations and capable of inhibiting the production of nitric oxide when tested in different strains, in which it is noteworthy that in both cell lines, tested samples obtained more satisfactory results when compared to the standard anti-inflammatory drug, dexamethasone.
Keywords: Inflamação; Óxido nítrico; Agentes anti-infecciosos; Plantas medicinais; Matéria médica vegetal; CIÊNCIAS DA SAÚDE: ODONTOLOGIA; Inflamação; Citotoxicidade; Óxido nítrico; Jucá; Ácido gálico